Civil Legal Relationship between Doctors and Patients in Online Health Services - Muhammad Arismunandar; Arman Lany (PDIH Untag Semarang, 2025)
The background to this research is unclear regulations regarding online healthcare services provided via the internet. Law Number 29 of 2004 concerning Medical Practice defines a patient as an individual who consults with a doctor directly or indirectly and requires the patient to provide honest and good faith information. However, its implementation in online services remains legally uncertain. This study aims to analyze the legal framework governing online healthcare services in Indonesia, examine whether doctor–patient relationships in online services comply with professional standards and medical ethics, and identify legal gaps arising from their implementation. The research employs a normative legal research method using statute and conceptual approaches, supported by primary, secondary, and tertiary legal materials obtained through literature review. The findings show that online healthcare services remain legally grounded in therapeutic agreements based on good faith, professionalism, and informed consent, even without direct physical interaction. However, current regulations are not yet comprehensive, particularly concerning electronic consent, platform responsibility, and dispute resolution mechanisms. In conclusion, although online healthcare services are legally permissible, clearer and more integrated regulations are required to ensure legal certainty, patient protection, and professional accountability in digital healthcare practices.